2018
DOI: 10.4102/jsava.v89i0.1556
|View full text |Cite
|
Sign up to set email alerts
|

Feather and skin development of ostriches Struthio camelus

Abstract: Information on feather and skin growth is important for the development of mathematical optimisation nutritional models for ostriches. Ostriches (n = 65) were subjected to a four-stage formulated growth diet programme (pre-starter, starter, grower and finisher), with declining protein and energy content. Nine birds were weighed, stunned, exsanguinated, defeathered, skinned and eviscerated at 1, 54, 84, 104, 115, 132 and 287 days of age. Feathers from four pre-selected locations on the body were harvested and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…The amino acid composition of feathers is different from the amino acid composition of body protein (Emmans 1989). The feather growth per region in relation to total feather growth of the current study compares favourably with similar results on one diet (Brand et al 2018a). This is a confirmation of results in this study, namely, that diet does not significantly affect feather growth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The amino acid composition of feathers is different from the amino acid composition of body protein (Emmans 1989). The feather growth per region in relation to total feather growth of the current study compares favourably with similar results on one diet (Brand et al 2018a). This is a confirmation of results in this study, namely, that diet does not significantly affect feather growth.…”
Section: Discussionsupporting
confidence: 91%
“…The linear relationship between the increase in skin size of all the birds and age ( Figure 2 ) is because of the fact that it was measured over a short interval and not up to the point where birds attain mature body weights. Generally, it is accepted that biological tissues, including ostrich skin, will follow a non-linear growth pattern (Brand et al 2018a ; Huxley 1932 ; McDonald et al 2002 ), but this will only become evident over extended periods of growth as the birds pass maturity (Mellet 1992 ). The fact that the skin size increases linearly for the first 244 days of the growth cycle can be a useful prediction instrument for slaughter birds and is in accordance with reports from Van Schalkwyk et al ( 2002 ), as they reported a linear increase in skin area with an increase in age.…”
Section: Discussionmentioning
confidence: 99%
“…El avestruz (Struthio camelus) es una especie de ave corredora originaria del continente africano que ha sido domesticado para fines productivos. Dentro de la industria del ejemplar son relevantes tres productos: carne, cuero y plumas; la carne es rica en proteínas y baja en grasas, mientras que el cuero y el plumaje son utilizados ampliamente en la industria de la moda (1,2,3). Los productos del animal también se implementan para decoración y la limpieza de máquinas y equipos finos (4).…”
Section: Introductionunclassified
“…Growing ostriches makes it possible to obtain a variety of products in a short period of time -juveniles, adult birds, hatching and food eggs, slaughter and processing products, down, feathers, etc. (Brand et al, 2018;Cooper, 2000). All ostrich species have high adaptive properties; the survival rate of young and adult birds is at the level of 75-85% (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%